KECAKAPAN AKADEMIK SISWA MELALUI PEMBELAJARAN BERBASIS PROYEK DI KELAS XI SMA BABUSSALAM - Lestar, Mulya Pudji Lestari Pudji (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research aimed to describe the students academic skills through the implementation of the project-based learning in the equation of progressive wave and stasionary wave in class XI MIA2 Senior High School Babussalam Pekanbaru. This study was conducted from March to June 2015 with research subjects are 30 students. The design of this research is pre-experimental design with one-shoot case study. Data collection instruments used in this research is the student work sheet and academic skill that consist of 12 objective questions by using absorption analysis. Score obtained from the student activity assessment at the first meeting were in good category (84.44%), score obtained in the activities of the second and third meetings are in very good category (85.56% and 86.67% ). While the score of a students academic skill test results is in good category (72.78%). So, it can be concluded that the implementation of project-based to train the studentâs academic skill in the equation of progressive wave and stasionary wave in class XI MIA2 Senior High School Babussalam Pekanbaru. Key Words: project-based learning, academic skills, progressive wave and stasionary wave.